The influence of player height on service performance in professional female tennis - Sánchez-Pay, A.; Ortega-Soto, J. A.; Sánchez-Alcaraz, B. (Coaching and Sport Science Review, 2019)
The aim of this study was to analyze the influence of female player height on service related parameters. Statistics on service performance and height of female players were gathered from the second round onwards in all Grand Slam tournaments. Findings showed that the taller the player, the higher the serve average speed, serve maximum speed in, number of aces and number of points won with the first service (%), however, the number of double faults will increase as well. The Wimbledon surface (grass, fast court) favours taller players, who win a higher percentage of points with their first services here when compared to other surfaces. The findings of this study help to recognize the influence of height in female tennis in service related parameters, as well as the differences between the surfaces.